Grandidierella bonnieroides Stephensen, 1948 (Amphipoda, Aoridae)—first record of an established population in the Mediterranean Sea - Brutto, Sabrina Lo; Iaciofano, Davide; Lubinevsky, Hadas; Galil, Bella S. (Zootaxa, 2016)
The first record in the Mediterranean Sea of the invasive aorid amphipod crustacean Grandidierella bonnieroides is presented. A widespread circumtropical species, recorded off the Saudi coast of the Arabian Gulf, the Red Sea and the Suez Canal, it may have been introduced into the Mediterranean through the Suez Canal. This tube-builder species of soft bottoms recently established a population in the polluted Haifa Bay, Israel. Further, this is the first Mediterranean record of the genus.